The impact of digital platforms on dietary patterns: An analysis of the literature (Research, Society and Development, 2024)
Excessive use of digital media can significantly impact the food conduct of young people and adults, bringing negative consequences to the food and mental state of individuals. The aim of this study is to find out how digital platforms influence the dietary pattern of young people and adults. An integrative literature review was performed on the impact of digital platforms on the eating pattern associated with the predominant eating behavior in the PubMed and Google Academic data references. National and international studies were selected published from 2010 to 2024, in English and Portuguese. Boolean operators “food behavior” and “social media” were also used to sum up and cross the terms related to food behavior, food standard, digital media and social networks. The verified studies sought to evaluate the repercussion of the use of digital platforms, acting positively or negatively, taking into account food aspects and behavioral conduct at different levels. It is noteworthy that other consequences of the use of digital platforms in the food standard were denoted, such as image distortion and body perception. Instagram runs among the most accessed tools. Therefore, the aesthetic issue of a fervent interference in the behavior of body perception in women and the standards imposed by society is emphasized. It is essential to emphasize the relevance of the discussion about the food standard and the entry to digital means in contemporary society, encompassing all social classes, in particular, in the group of women.